2016
DOI: 10.5958/0974-4576.2016.00040.2
|View full text |Cite
|
Sign up to set email alerts
|

Citrus infestation by the black scale,Parlatoria ziziphiLucas (Homoptera: Diaspididae) in Tlemcen, Algeria

Abstract: The study of citrus infestation by the black scale Parlatoria ziziphi Lucas 1853 (Homoptera, Diaspididae) is realized between 2012 and 2013 on two citrus varieties (Thomson and Portuguese) in El Fehoul station in Tlemcen in the NorthWest of Algeria. This study shows that Parlatoria ziziphi is present in both varieties and the upper surface of leaves is is always more infested than the lower surfacess. In terms of leaves infestation rates, it's very important at the southern exposure and the center of the plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This obtained result may be due to the response to light trend. These results are in agreement with those of Tawfeek and Abu-Shall, 2010;Chouih et al, 2011 andTaibi et al, 2016 .They reported that the average numbers of scales on the upper surface of leaf were more abundant than that on lower one. The occurrence percentages of P. ziziphus per leaf were 85.8% for the upper surface and 14.2% for the lower one.…”
Section: Preferable Leaf Surfacesupporting
confidence: 92%
“…This obtained result may be due to the response to light trend. These results are in agreement with those of Tawfeek and Abu-Shall, 2010;Chouih et al, 2011 andTaibi et al, 2016 .They reported that the average numbers of scales on the upper surface of leaf were more abundant than that on lower one. The occurrence percentages of P. ziziphus per leaf were 85.8% for the upper surface and 14.2% for the lower one.…”
Section: Preferable Leaf Surfacesupporting
confidence: 92%
“…The Black Parlatoria Scale (BPS), Parlatoria ziziphi (Lucas, 1853) has often been a major threat to citrus crops ( Citrus spp. : Rutaceae) in various parts of the world and has an important economic impact on citrus fruit production (Talhouk, 1975; EPPO, 2015; García Morales et al ., 2016; Taibi et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%